2009
DOI: 10.1111/j.1365-2265.2008.03365.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the SHBG gene contribute to the interindividual variation of sex steroid hormone blood levels in young, middle‐aged and elderly men

Abstract: Our findings show that and the (TAAAA)(n)-repeat and the Asp327Asn polymorphism contribute to the genetically determined interindividual variation in total serum T levels in healthy men through variation in SHBG concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 38 publications
1
32
1
Order By: Relevance
“…Although in vitro studies have shown that the (TAAAA) 6 allele reduces SHBG gene expression (22), opposite in vivo findings in men are consistent. Our findings confirm the three previous findings on higher SHBG levels in association with shorter TAAAA repeats (28,34,35), but not a very recent finding on their association with rs6259 (37). The association of the two CYP19A1 polymorphisms (rs11575899 and rs727479) with lower E 2 levels and elevated levels of free and bioavailable T matches well because the potent negative feedback action of E 2 on LH secretion should be suppressed, resulting in elevated T level (38).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although in vitro studies have shown that the (TAAAA) 6 allele reduces SHBG gene expression (22), opposite in vivo findings in men are consistent. Our findings confirm the three previous findings on higher SHBG levels in association with shorter TAAAA repeats (28,34,35), but not a very recent finding on their association with rs6259 (37). The association of the two CYP19A1 polymorphisms (rs11575899 and rs727479) with lower E 2 levels and elevated levels of free and bioavailable T matches well because the potent negative feedback action of E 2 on LH secretion should be suppressed, resulting in elevated T level (38).…”
Section: Discussionsupporting
confidence: 81%
“…The Asp356Asn (GAC 3 AAC) mutation in exon 8 of SHBG (rs6259) induces an additional consensus site for N-glycosylation, increasing circulatory half-life of the variant SHBG protein without affecting its steroid-binding affinity (33) or steady-state plasma levels (34), which our findings confirmed. Variable associations of this polymorphism, depending on age of men, were recently reported between SHBG and T levels (35). The only significant association we found with this polymorphism was the slightly but significantly (P Ͻ 0.01) elevated level of free T in heterozygotes.…”
Section: Discussioncontrasting
confidence: 35%
“…Alternatively, calculated concentrations of circulating free sex steroid may not accurately reflect local bioavailability of these hormones at the target tissue level (55)(56)(57). Calculation of free sex steroid concentrations assumes that the binding affinity between both sex steroids and SHBG is constant in the entire population and does not vary with age while, in reality, it may be affected by genetic variants or isoforms of SHBG, age and levels of other SHBG-binding steroids (54,(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Cousin et al (2004) studied a population of French women with hirsutism and found that homozygous patients for the six TAAAA repeat allele had higher serum SHBG levels compared with patients being homozygous for the nine TAAAA repeat allele, while SHBG levels of homozygous patients for the eight TAAAA allele lay between the two. This association between the six TAAAA allele and elevated SHBG levels was also found in healthy men (Turk et al, 2007;Eriksson et al, 2006;Vanbillemont et al, 2009).…”
Section: The (Taaaa)n Repeat Polymorphism In Shbg Promotermentioning
confidence: 55%